Human and environmental health concerns: What differences are required to make the difference? - Hinds, Joe (Frontiers in Psychology, 2022)
This article will take an interdisciplinary perspective on the combined concerns of human and planetary health. There will be an argument made here that in order for the mitigation of some of the more pressing human and planetary health problems, there is a need to entertain a ‘different’ perspective. We as a collective (of disciplines & people) desire change for the planet and its inhabitants and yet change is one of the least acceptable conditions of human experience. Developing an openness to alternative understandings of the human condition, to sit alongside the more ‘normal’ general social and cognitive perspectives that tend to be pervasive in the broad literature, is imperative if change is to occur. In essence we, as individuals, need to embrace the very concepts that we are promoting for the world. True to the roots of psychology, this paper will make the necessary (re) turn to the ‘particular’ and personal and a more inward rather than outward focus. Ideas derived from the wealth of psychotherapeutic literature and theory will be introduced and highlighted as important additions to the understanding, and therefore the mitigation, of both psychological and environmental dis-ease. Particular attention will be given to a 'depth' consideration of the human condition incorporating various pertinent ideas derived from the concept of the unconscious (e.g., defence mechanisms: Idealisation; Denial; & Rationalisation)